2021
DOI: 10.51273/esc21.2517117
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Postgraduate Trainees and Consultants working in Psychiatry Departments of Teaching Hospitals in Lahore, Pakistan

Abstract: Objective: To gauge the prevalence of burnout among postgraduate trainees and consultants working in psychiatry department, Services Hospital Lahore, Pakistan. Methods: 31 trainee and consultant psychiatrists in Services Hospital Lahore, Pakistan participated in this cross-sectional study. Abbreviated Maslach Burnout Inventory (aMBI) measured burnout. It consisted of 9 items, relating to emotional exhaustion, depersonalization and personal accomplishment. Each item is scored on a seven-point Likert scale. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They not only assessed burnout but also how it affected their levels of personal achievements. In their study, the results showed that despite burnout, doctors were still able to do their job effectively (Butt et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…They not only assessed burnout but also how it affected their levels of personal achievements. In their study, the results showed that despite burnout, doctors were still able to do their job effectively (Butt et al, 2021).…”
Section: Discussionmentioning
confidence: 97%